Governance: Blending Bureaucratic Rules with Day to Day Operational Realities; Comment on "Governance, Government, and the Search for New Provider Models" - David P Chinitz (Kerman University of Medical Sciences, 2016)
Richard Saltman and Antonio Duran take up the challenging issue of governance in their article "Governance, Government and the Search for New Provider Models," and use two case studies of health policy changes in Sweden and Spain to shed light on the subject. In this commentary, I seek to link their conceptualization of governance, especially its interrelated roles at the macro, meso, and micro levels of health systems, with the case studies on which they report. While the case studies focus on the shifts in governance between the macro and meso levels and their impacts on achievement of desired policy outcomes, they also highlight the need to better integrate the dynamics of day to day operations within micro organizations into the overall governance picture.